The spectrum of gastric cancer as seen in a large quaternary hospital in KwaZulu-Natal, South Africa - Benamro, F; Sartorius, B; Clarke, DL; Anderson, F; Loots, E; Olinger, L (Health and Medical Publishing Group, 2017)
Background. Gastric cancer (GC) is the fifth most commonly diagnosed cancer in the world, with the third-highest associated mortality. It has a varying geographical, ethnic and socioeconomic distribution. Objective. To assess the presentation and management of GC in the Durban metropolitan area, South Africa. Methods. A retrospective review of 131 patients treated at the quaternary Inkosi Albert Luthuli Central Hospital in Durban from 2009 to 2014 was performed. Results. The 131 patients were predominantly black African (n=59, 45.0%) and Indian (n=63, 48.1%). Gender was evenly distributed, with 72 males (55.0%) and 59 females (45.0%). The average age of the patients was 60 years (standard deviation 13.3). More than 70% were in advanced stages of cancer and were treated conservatively. There was no significant relationship between body mass index (BMI) and the position of the tumour (p=0.175). Creatinine and albumin levels differed significantly between the genders (p<0.001 and p=0.01, respectively). Conclusions. GC appears to have a disproportionately high prevalence among Indians in Durban, and the prevalence of GC appears to be slightly higher among males. Both these observations may simply reflect referral patterns and warrant further investigation. More than 70% of patients presented with advanced-stage disease, and anaemia was common. No relationship was found between BMI and the location of the tumour, although most of the cancers were in the body and distal part of the stomach.